Antibodies against Tumor Necrosis Factor (TNF) induce t-cell apoptosis in patients with inflammatory bowel diseases via TNF receptor 2 and intestinal CD14+ macrophages - Atreya, Raja Narayana; Zimmer, Michael; Bartsch, Brigitte; Waldner, Maximilian J.; Atreya, Imke; Neumann, Helmut; Hildner, Kai; Hoffman, Arthur; Kiesslich, Ralf; Rink, Andreas D.; Rau, Tilman T.; Rose-John, Stefan; et al. (Gastroenterology, 2011)
Background & Aims - The anti-tumor necrosis factor (TNF) antibodies infliximab, adalimumab, and certolizumab pegol have proven clinical efficacy in Crohn's disease. Here, we assessed the effects of anti-TNF antibodies on apoptosis in inflammatory bowel disease (IBD). - Methods - CD14+ macrophages and CD4+ T cells were isolated from peripheral blood and lamina propria mononuclear cells from patients with IBD and control patients. Cell surface markers and apoptosis were assessed by immunohistology and fluorescence-activated cell sorting techniques. - Results - Lamina propria CD14+ macrophages showed significantly more frequent and higher membrane-bound TNF (mTNF) expression than CD4+ T cells in IBD, whereas mTNF-dependent signaling proteins such as TNF receptor (TNFR) 2, TNFR-associated factor (TRAF) 2, and nuclear factor κB were induced in IBD mucosal CD4+ T cells. Most anti-TNF antibodies did not induce T-cell apoptosis in purified peripheral or mucosal CD4+ T cells. However, in contrast to etanercept, administration of all clinically effective anti-TNF antibodies resulted in a significant induction of T-cell apoptosis in IBD when lamina propria CD4+ T cells expressing TNFR2+ were cocultured with mTNF+ CD14+ intestinal macrophages. In contrast, no effects in control patients were noted. T-cell apoptosis in IBD occurred in vivo after treatment with adalimumab and infliximab, was critically dependent on TNFR2 signaling, and could be prevented via interleukin-6 signal transduction. Blockade of interleukin-6R signaling augmented anti-TNF-induced T-cell apoptosis in IBD. - Conclusions - Clinically effective anti-TNF antibodies are able to induce T-cell apoptosis in IBD only when mucosal TNFR2+ T cells are cocultured with mTNF-expressing CD14+ macrophages. The finding that anti-TNF antibodies induce apoptosis indirectly by targeting the mTNF/TNFR2 pathway may have important implications for the development of new therapeutic strategies in IBD.